Problems in treatment of children with burns on the basis of ICNP® - case report - Mess, Eleonora Anna; Filek, Aleksandra; Lisowska, Aleksandra (Journal of Education, Health and Sport, 2019)
Admission. Burn damage to the skin, mucosa, as well as tissues located deeper by the heat supplied from the outside. Thermal trauma is one of the most common reasons for reporting a child under 6 years of age to Hospital Emergency Departments. To assess the severity of burns take into account the degree and extent. Assessing the extent of burns most often used method: the hand, the rule of "nines" Wallace, the card Lund and Browder. In the struggle with burns importance of prompt and effective first aid. During hospitalization should be implemented proceeding analgesics, nutritional therapy and rehabilitation. In the pediatric patient care, it is important to include caregivers in treatment.Objective of the workThe aim of the study was to present the process of nurturing a child with burns using ICNP® terminology.Material and methods.The studies used case study and interview technique, observation, analysis of medical records. The study included 15 patients hospitalized month because of thermal burns.Conclusions:In the treatment of burns fast it plays a key role for first aid. Rehabilitation should be implemented as quickly as possible in order to avoid restriction of mobility, fast upright, prevention of contractures, and prevention against formation of hypertrophic scars. The family of the child plays an important role in the treatment process. Takes care of the patient during hospitalization, he cares for the patient actively participates in diagnostic tests, as well as a valuable source of information about the child's psychophysical response to painful stimuli. The tasks of a nurse who has the overall care of the child oparzonym should also educate the patient's family and place it on the self-care of a child scalded.